Living with rare genetic disease during the COVID-19 pandemic: A qualitative study of adolescents and young adults with Li-Fraumeni syndrome - Allison Werner-Lin; Payal P. Khincha; Ashley S. Thompson; Camella Rising; Alix Sleight; Catherine Wilsnack; Patrick Boyd; Alexandra Feldman; Rowan Forbes Shepherd; Sharon A. Savage (Rare)
Background: The COVID-19 pandemic caused large-scale shifts in healthcare access and delivery that impacted the availability of routine care, such as cancer screening. Vulnerable populations, including those with rare cancer-prone genetic disease, faced considerable difficulties in managing their cancer risk. Studies characterizing the specific impacts of the pandemic on physical, mental, and emotional well-being for individuals with rare cancer-prone syndromes are emerging. This study used a patient-centered perspective to characterize how young adults with Li-Fraumeni syndrome (LFS), an inherited cancer predisposition syndrome with nearly 100 % lifetime risk of cancer, managed their physical and mental health during the first year of the COVID-19 pandemic. Methods: This exploratory, qualitative cohort study was conducted between March and July of 2021 as part of the National Cancer Institute's Li-Fraumeni Study. Thirty adolescents and young adults (22 female, 8 male, median age 31 years, range 18–41) with a confirmed pathogenic TP53 variant completed a semi-structured qualitative interview. An interdisciplinary team conducted Thematic Content Analysis on verbatim transcribed data. Results: Most participants (22/30, 77 %) completed cancer screening during the first year of the pandemic, with a median perceived delay of 5 months (range 2–12 months) and with financial COVID-19-related burden (55 %). While participants reported satisfaction with telehealth-based services, they also reported challenges establishing new clinical relationships and a clear preference for in-person clinical care. Most participants reported negative or mixed impacts of COVID-19 on mental health (21/30, 70 %). Social network changes were reported by 22 (73 %), and almost all participants experienced negative or mixed emotions such as loss, grief, and isolation, to adaptations necessitated by COVID-19 in their social structure. Conclusions: The COVID-19 pandemic had detrimental effects on the physical, emotional, and social health in young adults with Li-Fraumeni, including disruptions in care. These data highlight the need for integrative strategies to be in place prior to future pandemics to prioritize and support vulnerable populations, such as those with rare disease, and to manage unforeseen large-scale shifts in healthcare access and social structure.